MODEL THINK TALK WRITE TERHADAP KEMAMPUAN ANALISIS SISWA SEKOLAH DASAR: STUDI EKSPERIMENTAL - Mu’alifah Mu’alifah; Rarasaning Satianingsih; Via Yustitia (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2020)
Analytical skills is the ability to describe the materials into parts or components that are more structured and easier to understand. Currently the students are still less than optimal in mastering the concepts of teaching materials. Mastery of concepts related to the ability of thinking tends to the analytical skills of students. TTW models can be used as an alternative to improve the analysis because this model is more emphasis on specialized structures designed to affect the pattern of interaction of students and has a goal to foster students' analytical skills. This study aims to determine the analytical skills of fourth grade students are taught using TTW models are significantly better than the students who are taught using a contextual model. This research is a quantitative research Quasi-Experimental Design The design Posttest-Only Control Design. The population in this study are all students of class IV SDN Ketabang Surabaya academic year 2019/2020. Data were analyzed using normality test, homogeneity test, a balance test and t test aided SPSS 22. The results showed that the analytical skills that are taught fourth grade students using the model significantly TTW better than the students who are taught using a contextual model SDN Ketabang  Surabaya.